(untitled) (Journal of Human Sciences, 2021)
The Fezzan region has an important geographical location that contributed to spread of Islam in the surrounding African regions and aspects. It is a rural community and the people of this region have a desert character. Nevertheless, it did not prevent people to settling in it. Where there are mountains, valleys and oases, and the city of Zuweila ,was the capital of the region ,Fezzan in the Islamic era ,and zuwayla developed the bani al-khattab who owned Fezzan from the beginning of the fourth century ah to the year 306 ad they are distinguished by their own social habits in holding feasts, weddings and funerals , which do not differ much from the social customs in the rest of the regions. They are distinguished by their own social habits in holding feasts, weddings .and funerals, which are not different from the social habits in other regions Therefore, I dealt with in this research showing the aspects of social life in the Libyan regions of Fezzan, Tripoly and Barga. During the Islamic judgement and the relation between them, through the study of social classes, habits and traditions for each region, especially since all regions speak Arabic with the exception of a few of them speaking in addition to the Arabic language, the Berber and Tuareg language. This is addition to knowing what each region characterized to reflect the aspects of social life in it and to know the extent of .interconnection, agreement and difference in the regions And my goal of this study was to know the habits and traditions that reflect the reality of social life within the Libyan regions, especially since the social relationship between the .Libyan regions was linked to each other during the Islamic judgement The importance and the reason for choosing the studying lies in standing and highlighting the social history of libya and showing the extent of cohesion and interconnection between the members of its regions, especially since most of the studies were concerned with political and economic aspects and only a small aspect was shown about life, which is considered one of .the vital topics, so I highlighted it I followed a historical narrative method and analysing the information to arrive at results .that benefit the research.